2012
DOI: 10.1007/s00167-012-2139-7
|View full text |Cite
|
Sign up to set email alerts
|

TKA outcomes after prior bone and soft tissue knee surgery

Abstract: This study confirms that prior knee surgery could be considered a clinical condition predisposed to higher postoperative complication rate in primary TKA compared to the no prior surgery group. After analysing the three study groups, group C showed a higher rate of postoperative local complications and lower IKS knee scores, while the group B showed the poorest postoperative mean values of knee flexion as well as the need for extended surgical approach (TTO approach) was more prevalent in this study group. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…Primary TKA is a reliable procedure for the improvement of pain and function. 17,18 A retrospective study compared the results of TKA in patients with prior bony or soft tissue surgical procedures with primary TKA without prior proce- 19 The IKS knee score improvements were lower in the groups with prior procedures, with the soft tissue procedure group showing the smallest IKS change. A study of patients with a history of 2 or more arthroscopic procedures before TKA did not show a difference in KSS score improvement compared with primary TKA without prior procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary TKA is a reliable procedure for the improvement of pain and function. 17,18 A retrospective study compared the results of TKA in patients with prior bony or soft tissue surgical procedures with primary TKA without prior proce- 19 The IKS knee score improvements were lower in the groups with prior procedures, with the soft tissue procedure group showing the smallest IKS change. A study of patients with a history of 2 or more arthroscopic procedures before TKA did not show a difference in KSS score improvement compared with primary TKA without prior procedures.…”
Section: Discussionmentioning
confidence: 99%
“…33 In a study of prior soft tissue procedures with 10 years of follow-up, a significantly higher number of postoperative complications and an insignificantly lower survivorship rate (94.8% vs 98.1% in the control group, respectively) were identified. 19 A study of 35 knees with osteochondral allograft transplantation before TKA demonstrated a 17% revision rate due to aseptic loosening. 34 In the current series, 1 (5%) patient with prior MFX developed polyethylene wear requiring tibial liner exchange at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…They had been scheduled for total knee arthroplasty (TKA). Diagnosis was based on clinical history, physical examination and radiographic evaluation that included comparative anteroposterior knee view with monopodal support, bilateral posteroanterior view at 45°flexion in weight-bearing, comparative lateral view at 30°flexion, axial view at 30°flexion and stress valgus and varus X-ray using a Telos system [15]. Malalignment was confirmed by measuring mechanical axis of the leg, hip-knee-ankle (HKA) angle, from bilateral weightbearing anteroposterior long-leg films.…”
Section: Participantsmentioning
confidence: 99%
“…Knee flexion range is a useful measure and accurate indicator of TKA outcomes. Previous clinical studies have reported mean final knee flexions ranging from 100° to 130°, regardless of the surgical technique or prosthetic design [32,40,42].…”
Section: Introductionmentioning
confidence: 99%